Fast Universal Spectrophotopolarimeter for Robotic Telescopes - Vladimir Plokhotnichenko; Grigory Beskin; Sergey Karpov; Sergey Bondar; Vjacheslav de-Boer; Alexandre Lioubetski; Dmitry Badjin (Advances in Astronomy)
FUSP is the automatic multimode spectrophotopolarimeter aimed to the study of fast optical transients in the photometric, photopolarimetric (instant measurement of linear polarization), and spectropolarimetric (with or without the slit) modes. The mode change is automatic depending on the transient brightness and the purposes of the observations and may be performed in half a second. The instrument may be equipped with either fast EM-CCD or a position-sensitive detector which may provide temporal resolution up to 1 microsecond. FUSP is the robotic instrument for the robotic telescopes.